Complete mitochondrial genome of the gray red-backed vole (Myodes rufocanus) and a complete estimate of the phylogenetic relationships in Cricetidae. (2nd January 2017) - Lu, Taofeng; Zhu, Minghao; Yi, Cheng; Si, Changde; Yang, Chunwen; Chen, Hongyan
Abstract: Myodes rufocanus belongs to the genera Myodes within the subfamily Cricetidae, its complete mitochondrial genome is 16 487 bp in length, containing 12S rRNA gene, 16S rRNA gene, 22 tRNA genes, 13 protein-coding genes and 1 control region as other Cricetidae species. Results of phylogenetic analysis showed that Myodes had close relationship with Eothenomys, and had distant relationship with Microtus, Cricetulus, Wiedomys, Akodon and other genera. This study verifies the evolutionary status of Myodes rufocanus in Myodes at the molecular level. The mitochondrial genome would be a significant supplement for the M. rufocanus genetic background analysis and experimental animalization.